Subtitle Translation: Cultural Components in the Translation of the Film Qu'est-ce qu'on a fait au bon Dieu? - ÜNSAL, GÜLHANIM (SELCUK UNIV, FAC LETTERS, 2018)
Subtitle translation which is one of the oldest types of translation, can be defined as translation of audio-visual constituents in the source language simultaneously into the target language in a limited duration. In this translation type, the source text should be translated into the target text without meaning and information loss, in a correct and understandable way, simultaneously with picture and sound. In subtitle translation, which is a type of both intralingual and interlingual translations, audiovisual elements in the source text should be translated in a simple, clear and effective way in a short time in accordance with grammar and syntax rules of the target language. What the audience reads in the target language is what they hear in the source language. Subtitle translation which is presented together with the original sound of the movie is a bare translation; therefore it is open to criticism in this respect as well. In addition, it is observed that there is a challenge being faced in subtitle translation to convey cultural components. Based on the translation approach adopted, subtitle translation can be target-oriented and foreignization between the audience and the product belonging to a different culture can disappear. On the other hand, it can be source-oriented and foreignization between the audience and the product can occur. And yet, translator is the person who decides how to represent a foreign culture and what kind of strategy to follow in the translation of the cultural components. From this point forth, the cultural components in subtitle translation will be examined in this study through translator decisions in the light of Venuti's domestication and foreignization approaches. For this purpose, in the translation of cultural components from French to Turkish in the film called Qu'est-ce qu'on a fait au bon Dieu?, it was attempted to determine the restrictions that the translator was exposed to, which strategies were followed and what kind of decisions were made by the translator.
Keywords: Subtitle translation; cultural components; translation strategies; translator